2022
DOI: 10.1186/s12915-022-01469-y
|View full text |Cite
|
Sign up to set email alerts
|

Histone modifications and DNA methylation act cooperatively in regulating symbiosis genes in the sea anemone Aiptasia

Abstract: Background The symbiotic relationship between cnidarians and dinoflagellates is one of the most widespread endosymbiosis in our oceans and provides the ecological basis of coral reef ecosystems. Although many studies have been undertaken to unravel the molecular mechanisms underlying these symbioses, we still know little about the epigenetic mechanisms that control the transcriptional responses to symbiosis. Results Here, we used the model organism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Furthermore, proteomic studies comparing symbiotic with aposymbiotic Aiptasia, as well as symbiotic Aiptasia containing homologous versus heterologous symbionts, have also revealed important nutrient exchange mechanisms, including lipid and sterol transport by Niemann-Pick type C2 (NPC2) protein, inorganic carbon transport, and nitrogen cycling by members of the glutamine synthetase/glutamine oxoglutarate aminotransferase (GS/GOGAT) pathway (111,143). In Aiptasia hosting a homologous symbiont strain, a deep analysis into host gene regulation demonstrated that the activation of histone modifications was associated with genes upregulated in symbiosis, including glucose metabolism, nitrogen transport, and members of mTORC1, among others (107). At the cellular level, single-cell RNA sequencing of the stony coral S. pistillata demonstrated that symbiont-containing cells upregulate lysosome-associated genes, as well as genes involved in lipid sensing and metabolism, from transport to fatty acid elongation (77).…”
Section: Cellular and Molecular Mechanisms Of Nutrient Exchangementioning
confidence: 99%
“…Furthermore, proteomic studies comparing symbiotic with aposymbiotic Aiptasia, as well as symbiotic Aiptasia containing homologous versus heterologous symbionts, have also revealed important nutrient exchange mechanisms, including lipid and sterol transport by Niemann-Pick type C2 (NPC2) protein, inorganic carbon transport, and nitrogen cycling by members of the glutamine synthetase/glutamine oxoglutarate aminotransferase (GS/GOGAT) pathway (111,143). In Aiptasia hosting a homologous symbiont strain, a deep analysis into host gene regulation demonstrated that the activation of histone modifications was associated with genes upregulated in symbiosis, including glucose metabolism, nitrogen transport, and members of mTORC1, among others (107). At the cellular level, single-cell RNA sequencing of the stony coral S. pistillata demonstrated that symbiont-containing cells upregulate lysosome-associated genes, as well as genes involved in lipid sensing and metabolism, from transport to fatty acid elongation (77).…”
Section: Cellular and Molecular Mechanisms Of Nutrient Exchangementioning
confidence: 99%
“…This is compatible with recent findings in Arabidopsis that the H3K4me3 mark was significant in TSS and genic regions [ 60 , 65 , 68 , 69 ], indicating that domains might be conserved in organisms [ 45 , 70 , 71 ]. Species-specific H3K4me3 distribution patterns were reported in plants, while some genomes were highly methylated, and a few were sparsely methylated [ 72 74 ]. The epigenetic mechanisms often act in a coordinated fashion to influence plant functions.…”
Section: Discussionmentioning
confidence: 99%